2020
DOI: 10.1097/md.0000000000018841
|View full text |Cite
|
Sign up to set email alerts
|

Rs10757274 gene polymorphisms in coronary artery disease

Abstract: Background: It has been reported the rs10757274 SNP (present on locus 9p21 in the gene for CDKN2BAS1) might be associated with susceptibility to coronary artery disease (CAD). Owing to mixed and inconclusive results, we conducted a meta-analysis to investigate the association between rs10757274 polymorphism and the risk of CAD. Objectives: The present study aimed to investigate the relationship between rs10757274 polymorphism and the risk of CAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“… 31 However, Hu et al 17 and Xu et al 37 conducted meta-analysis studies and concluded that the rs10757278 polymorphism might serve as a genetic marker for CAD. Our research results are in line with the Niemiec et al 35 study, which showed that rs10757278, independent of traditional risk factors, affected CAD susceptibility. 16 , 38–40 In 2011, the rs10757278 polymorphism was first evaluated in a PAGE analysis to assess its association in two populations according to linkage disequilibrium, and the correlation coefficient high.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 31 However, Hu et al 17 and Xu et al 37 conducted meta-analysis studies and concluded that the rs10757278 polymorphism might serve as a genetic marker for CAD. Our research results are in line with the Niemiec et al 35 study, which showed that rs10757278, independent of traditional risk factors, affected CAD susceptibility. 16 , 38–40 In 2011, the rs10757278 polymorphism was first evaluated in a PAGE analysis to assess its association in two populations according to linkage disequilibrium, and the correlation coefficient high.…”
Section: Discussionsupporting
confidence: 92%
“…The rs10757278 polymorphism shows both positive 35 , 36 and negative associations. 31 However, Hu et al 17 and Xu et al 37 conducted meta-analysis studies and concluded that the rs10757278 polymorphism might serve as a genetic marker for CAD.…”
Section: Discussionmentioning
confidence: 99%
“…12 More and more evidence indicated that single-nucleotide polymorphism (SNP) might impact the disease's clinical symptoms and prognosis. 13,14 Studies had shown that different genotypes of SNPs were related to the pathogeny and prognosis of AML. [15][16][17] Many SNPs had been identified in the human GATA2 gene, including rs2335052, rs3803, rs2713604 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidence indicated that single‐nucleotide polymorphism (SNP) might impact the disease's clinical symptoms and prognosis 13,14 . Studies had shown that different genotypes of SNPs were related to the pathogeny and prognosis of AML 15‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…Within this chromosomal locus, we chose rs10757274 A/G as the genetic marker for heart disease. Those who carry the minor allele A on rs10757274 at 9p21 have a lower odds ratio (.69-.81) for incident CHD (Xu et al, 2020) and those who carry the risk allele G (vs. A) have a hazard ratio of 1.10 to 1.22 for different racial and ethnic samples (Franceschini et al, 2011). For T2D, the three most highly validated genomic markers at the time of study design were: TCF7L2, KCNJ11, and PPARG (Craddock & Jones, 2007).…”
mentioning
confidence: 99%